Gerenciamento de projetos de engenharia de manutenção em edifícios públicos: uma abordagem transdisciplinar - Jarem Guarany Gomes Junior (2012)
This work employs a transdisciplinary approach to the elaboration and supervision process of building maintenance projects in public buildings to analyze the conduct and posture of professionals involved in the several stages. The present study was developed from the analysis of the evolution of the states role in public policies and of the relevance of political, social and power related aspects to the success of publicmanagement projects. Subjects regarding building maintenance and engineering projects management innovation were considered through a transdisciplinary analysis. A surveying was conducted about the edified space occupied by the judiciary and about the attendance model to the building maintenance that existed before the elaboration and implantation of the building maintenance project. An evaluation of the hiring models of maintenance in public buildings was established as well as an analysis of the processes and postures of Courthouses internal agents involved in building maintenance. The field surveying results allied with theoretic foundations based on the consulted authorsallow to establish elements which demonstrate the importance of economical, political, administrative and power aspects in the elaboration and implantation of building maintenance projects on the judiciary buildings. Considering the transdisciplinary approach on the subject, through action propositions for the building maintenance hiring project, the importance of a cultural change and a proactive and collaborative attitude by the public agents in order to attain effectiveness in the public engineering project of building maintenance could be confirmed.